2019
DOI: 10.3389/fnbeh.2019.00107
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Motor Function in the Tg4-42 Mouse Model of Alzheimer’s Disease

Abstract: Alzheimer’s disease (AD) is a neurodegenerative disorder and the most common form of dementia. Hallmarks of AD are memory impairments and cognitive deficits, but non-cognitive impairments, especially motor dysfunctions are also associated with the disease and may even precede classic clinical symptoms. With an aging society and increasing hospitalization of the elderly, motor deficits are of major interest to improve independent activities in daily living. Consistent with clinical findings, a variety of AD mou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 109 publications
(158 reference statements)
5
37
0
Order By: Relevance
“…Open field (OF), rotarod, MWM, and Y-maze tests were conducted for determining the effect of 3NCP on the behavior of the test animals in terms of locomotion, motor coordination, hippocampal-dependent spatial learning and memory, and spatial recognition memory, respectively [ 35 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Open field (OF), rotarod, MWM, and Y-maze tests were conducted for determining the effect of 3NCP on the behavior of the test animals in terms of locomotion, motor coordination, hippocampal-dependent spatial learning and memory, and spatial recognition memory, respectively [ 35 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Alzheimer disease symptoms refer also to motor dysfunctions which can appear before classic clinical symptoms 26,27 . M. inermis may be used to protect motor memory.…”
Section: Discussionmentioning
confidence: 99%
“…However, an analysis of the physical activity level at weeks 7 to 8 in the middle of the treatment period revealed that WT mice in general showed increased levels of physical activity compared to Tg4-42 mice. This could be likely attributed to a motor phenotype in the Tg4-42 mice, that becomes evident in tasks addressing motor coordination, such as balance beam, or in general motor performance and motor learning, which have been assessed using the rotarod task (Hüttenrauch et al., 2016a; Wagner et al., 2019). This might suggest that reduced running distance could account for the observed decrease in hippocampal neurogenesis in Tg4-42 mice.…”
Section: Discussionmentioning
confidence: 99%